Pyrosequencing reveals changes in soil bacterial communities after conversion of Yungas forests to agriculture - Montecchia, Marcela Susana (2015)
Fil: Montecchia, Marcela Susana. Universidad de Buenos Aires. Facultad de Agronomía. Instituto de Investigaciones en Biociencias Agrícolas y Ambientales (INBA). Buenos Aires, Argentina.